PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER, SALES GROWTH, DAN NET PROFIT MARGIN TERHADAP RETURN ON EQUITY - Anggraeni, Putri Pangestika; Adi, Suyatmin Waskito (ITB AAS Indonesia Surakarta, 2025)
Indonesia's rapid economic development encourages companies to maximize growth and achieve profits. In the face of economic dynamics, monitoring financial performance is crucial, along with innovation to adapt. Companies in the healthcare sector are unique in that they are influenced by regulations, technological developments, and the public's need for healthcare services. During the pandemic, the sector has become particularly important due to increased demand for medicines, vitamins and medical equipment. The increase in sales of healthcare products is reflected in the financial reports available on the Indonesia Stock Exchange, allowing investors to evaluate financial performance through financial ratio analysis. This research is expected to provide validation, insight for investment decision making, and help companies improve operational efficiency in order to increase ROE as an indicator of profitability. This study was conducted to see the effect of current ratio, debt to equity ratio, total asset turnover, sales growth, and net profit margin on return on equity in healthcare companies listed on the IDX in 2019-2023. The method used in this research is multiple linear regression analysis. This study shows that Debt to equity ratio, Total asset turnover, Net profit margin affect return on equity, while Current ratio and Sales growth have no effect on return on equity.